Nesfatin-1 ameliorates oxidative brain damage and memory impairment in rats induced with a single acute epileptic seizure - ARABACI TAMER, SEVİL; KOYUNCUOĞLU, TÜRKAN; AKAKIN, DİLEK; YÜKSEL, MERAL; YEGEN, BERRAK (My University, 2022)
© 2022Aims: We aimed to investigate putative neuroprotective effects of nesfatin-1 on oxidative brain injury and memory dysfunction induced by a single epileptic seizure and to compare these effects with those of antiepileptic phenytoin. Main methods: Wistar albino rats were randomly divided into a control group and pentylenetetrazole (PTZ)-seizure groups pretreated intraperitoneally (ip) with saline or nesfatin-1 (NES-1; 0.3, 1 or 3 μg/kg/day) or phenytoin (PHE; 40 mg/kg/day) or PHE + NES-1 (0.3 μg/kg/day) at 30 min before the single-dose PTZ injection (45 mg/kg; ip). All treatments were repeated at the 24th and 48th h of the provoked epileptic seizure. Passive-avoidance test was performed to assess memory function. The rats were decapitated at the 72nd hour of seizures and brain tissues were analyzed for histopathological changes and for measuring levels of malondialdehyde, glutathione, myeloperoxidase activity and reactive oxygen/nitrogen species. Key findings: In parallel to the effects of phenytoin, NES-1 reduced seizure score, elevated antioxidant glutathione content, depressed generation of nitric oxide and protected against seizure-induced neuronal damage. Additionally, increased malondialdehyde levels and elevated glial fibrillary acidic protein immunoreactivity in the cortex and hippocampus were decreased and memory dysfunction was improved by NES-1. However, NES-1 had no impact on myeloperoxidase activity or production of reactive oxygen species in the brain. Significance: The findings of the present study demonstrate that nesfatin-1 treatment provides neuroprotection against seizure-induced oxidative damage and memory dysfunction by inhibiting reactive nitrogen species and upregulating antioxidant capacity, indicating its potential in alleviating memory deficits and increasing the effectiveness of conventional anti-convulsant therapies.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Moleküler Biyoloji ve Genetik; FARMAKOLOJİ VE ECZACILIK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; MOLECULAR BIOLOGY & GENETICS; PHARMACOLOGY & PHARMACY; BIOCHEMISTRY & MOLECULAR BIOLOGY; General Biochemistry, Genetics and Molecular Biology; General Pharmacology, Toxicology and Pharmaceutics; Nesfatin-1; Seizure; Oxidative injury; Memory dysfunction; Apoptosis; NITRIC-OXIDE; ISCHEMIA-REPERFUSION; HIPPOCAMPAL-NEURONS; SATIETY MOLECULE; KAINIC ACID; STRESS; INJURY; ANTIOXIDANT; APOPTOSIS; PROTECTS